Plasma adenosine deaminase-1 and -2 activities are lower at birth in Papua New Guinea than in The Gambia but converge over the first weeks of life - Kouyate, Thomas S.; Nguyen, Athena N.; Plotkin, Alec L.; Ford, Rebeca; Idoko, Olubukola T.; Odumade, Oludare A.; Masiria, Geraldine; Jude, Joe; Diray-Arce, Joann; McEnaney, Kerry; Ozonoff, Al; Steen, Hanno; et al. (Frontiers in Immunology, 2024)
Dynamic cellular and molecular adaptations in early life significantly impact health and disease. Upon birth, newborns are immediately challenged by their environment, placing urgent demands on the infant immune system. Adenosine deaminases (ADAs) are enzymatic immune modulators present in two isoforms -ADA-1 and ADA-2. Infants exhibit low ADA activity, resulting in high plasma adenosine concentrations and a consequent anti-inflammatory/anti-Th1 bias. While longitudinal studies of plasma ADA have been conducted in infants in The Gambia (GAM), little is known regarding ADA trajectories in other parts of the world. Herein, we characterized plasma ADA activity in an infant cohort in Papua New Guinea (PNG; n=83) and compared to ontogeny of ADA activity in a larger cohort in GAM (n=646). Heparinized peripheral blood samples were collected at day of life (DOL) 0, DOL7, DOL30, and DOL128. Plasma ADA-1, ADA-2, and total ADA activities were measured by chromogenic assay. Compared to GAM infants, PNG infants had significantly lower ADA-1 (0.9-fold), ADA-2 (0.42-fold), and total ADA (0.84-fold) activities at birth which converged by DOL30. Overall, discovery of a distinct baseline and a consistent pattern of increasing plasma ADA activity in early life in two genetically and geographically distinct populations validates and extends previous findings on the robustness of early life immune ontogeny.